Strategi Kepala Tata Usaha dalam Meningkatkan Mutu Layanan Administrasi di Madrasah tsanawiyah Laboratorium Kota Jambi - Sismawati Sismawati; Armida Armida; Idariyanti Idariyanti (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to identify and analyze the strategies implemented by the head of administration in improving the quality of administrative services at Madrasah Tsanawiyah Laboratorium, Jambi City. Improving the quality of institutional administrative services aims to support the overall quality of the madrasah. Based on national education standards set by the Ministry of Education and Culture, good school quality must also be reflected in the aspect of administrative services. Therefore, the leadership role of the head of administration is very important in designing and implementing strategies that support the achievement of the institution's vision and goals. This study uses a qualitative descriptive approach from an educational perspective. The main objectives of this study are to explore the process of strategic planning, implementation, strategy evaluation, and supporting and inhibiting factors in improving administrative services. Data collection was carried out through interviews, observations, and documentation. Data analysis techniques used include data reduction, data presentation, and verification, with data validity guaranteed through triangulation of sources, methods, and data. The results of the study indicate that the planning strategy used by the head of administration focuses on the principle of "the sooner the better," through friendly, innovative service, process simplification, service acceleration, and planning the use of ABK (Workload Analysis) guidelines. The strategy implementation is carried out in an integrated manner through regular meetings, active coordination with the head of the madrasah, the use of digital applications, and an effective work system. Evaluations are carried out daily by the head of the madrasah directly or online via WhatsApp, and using SWOT analysis to assess service progress. Supporting factors include staff training, open communication, and regular evaluations. Meanwhile, the main inhibiting factor is the shortage of administrative staff, which causes an excessive workload on the head of administration who also has teaching duties.